Drama Sessions for Primary Schools and Drama Clubs. - Day, Alison (Taylor & Francis, 2011)
Drama Sessions for Primary Schools and Drama Clubs is an indispensable guide designed to help you run effective and enjoyable drama sessions in your primary school for a whole academic year.